Quantitative LC-MS/MS method development and validation for the estimation of neratinib: application to bioavailability study in healthy rabbits - Lakshmi Kanth M; Raj Kamal B (International Journal of Pharmacy and Analytical Research, 2022)
A sensitive, simple and liquid chromatography – tandem mass spectrometry (LC- MS/MS) method was developed and validated for the fast quantification of Neratinib (NRTB) in human plasma. The developed method was successfully applied to bioavailability study in healthy rabbits. The analyte and Crizotinib (CZNB) internal standard (IS) were separated from 200 mL of plasma sample by opting the protein precipitation as an extraction method with methanol. Chromatographic resolution was resolved with phenominex C18(50mm×4.6 mm, 4 mm) analytical nonpolar column and a mobile phase mixture of 10mM ammonium acetate, acetonitrile and methanol in the ratio of 20:30:50. Mobile phase flow from the column was fixed at 0.8 ml/min. The overall analysis time is promising compared to other reported procedures for Neratinib. From in vivo studies NRTB was shown Tmax of 6.05±0.027 and mean Cmax, AUC0®t and AUC0®a for test formulation is 295.83±39.066, 856.70 ± 153.16 and 1652.447 ± 205.06 respectively. The developed and validated research method was successfully applied in bioavailability studies in healthy rabbits.